AVALIAÇÃO DO PADRÃO COMPORTAMENTAL DE MACACOS-PREGO (Cebus apella) MANTIDOS EM CATIVEIRO - Denise Nunes Araujo; Sônia Cristina Rossetti de Melo; Ana Claudia Ambiel Corral Camargo 1 (Colloquium Agrariae, 2010)
This study aimed to identify, describe and analyze the behavioral patterns of capuchin monkeys in captivity. Were observed seven individuals of the species Cebus apella, six males (four adults, one sub-adult and one juvenile) and one adult female. Initially, observations were performed by using the ad libitum for preparing the ethogram; after, were used the scan sampling method to establish the behavioral patterns during four days over a period of 8 hours and 50 minutes consecutively, in the period from 7:00 a.m. to 16:00 p.m. Among the observed behaviors, Rest, Picking, Drinking Water, Foraging, Scratching, Displacement, Observation, Play and Use and/or handling of tools showed significant differences in the statistical analysis were the behaviors (P<0.05). The behaviors more frequent were Displacement (55%), Foraging (16%), Play (14.58%), Observation (14.29%) and Scratching (13.39%). The Feeding behavior was not significantly different, and this change may have been influenced by the timing and amount of food provided.